Detection of Burkholderia pseudomallei with CRISPR-Cas12a based on specific sequence tags - Zhang, Jia-Xin; Xu, Jian-Hao; Yuan, Bing; Wang, Xiao-Dong; Mao, Xu-hu; Wang, Jing-Lin; Zhang, Xiang-Li-Lan; Yuan, Yuan (Frontiers in Public Health, 2023)
Melioidosis is a bacterial infection caused by Burkholderia pseudomallei (B. pseudomallei), posing a significant threat to public health. Rapid and accurate detec-tion of B. pseudomallei is crucial for preventing and controlling melioidosis. However, identifying B. pseudomallei is challenging due to its high similarity to other species in the same genus. To address this issue, this study proposed a dual-target method that can specifically identify B. pseudomallei in less than 40 minutes. We analyzed 1722 B. pseudomallei genomes to construct large-scale pan-genomes and selected specific se-quence tags in their core genomes that effectively distinguish B. pseudomallei from its closely related species. Specifically, we selected two specific tags, LC1 and LC2, which we combined with the Clustered Regularly Interspaced Short Palindromic Re-peats (CRISPR)-CRISPR associated proteins (Cas12a) system and recombinase pol-ymerase amplification (RPA) pre-amplification. Our analysis showed that the du-al-target RPA-CRISPR/Cas12a assay has a sensitivity of approximately 0.2 cop-ies/reaction and 10 fg genomic DNA for LC1, and 2 copies/reaction and 20 fg ge-nomic DNA for LC2. Additionally, our method can accurately and rapidly detect B. pseudomallei in human blood and moist soil samples using the specific sequence tags mentioned above. In conclusion, the dual-target RPA-CRISPR/Cas12a method is a valuable tool for the rapid and accurate identification of B. pseudomallei in clinical and environmental samples, aiding in the prevention and control of melioidosis.